Changes in Child and Adolescent Needs and Strengths (CANS) scores over time: A systematic review. (May 2020) - Sokol, Rebeccah L.; Li, Juliann; Victor, Bryan G.; Miller, Alison L.; Ryan, Joseph P.; Perron, Brian E.
Highlights: Only seven studies assessed CANS scores over time following CANS-informed services. Risk Behaviors, Functioning, and Child Strengths domain scores improved over time. For most CANS domains, there was little to no evidence for improvement over time. Future research needs to assess further the CANS tool and CANS-informed care models. Abstract: The Child and Adolescent Needs and Strengths (CANS) is an assessment tool that child-serving settings have used with children and their families to identify areas for intervention and monitor service outcomes over time. Despite its widespread application, the field knows little about how children's CANS scores change over time in settings that provide CANS-informed services. The current study systematically reviewed changes in CANS scores over time in the existing longitudinal services research. Seven studies met inclusion criteria, and these studies assessed a total of 11 CANS domains: Problems, Risk Behaviors, Functioning, Mental Health, Traumatic Stress Symptoms, Behavioral/Emotional Needs, Acculturation, Externalizing, Child Strengths, Care Intensity, Caregiver Strengths, and Caregiver Needs and Strengths. Overall, the existing evidence on longitudinal CANS applications is limited. Scores within three CANS domains–Risk Behaviors, Functioning, and Child Strengths–improved over time in five of the seven studies. For the majority of CANS domains, however, there was little to no evidence for improvement over time following CANS-informed services. We discuss implications for practice and future research.